Santiago de Cuba, pionero de la orientación profesional en Cuba - Hernández Cardoza, Daniela (2024)
The research presented aimed to analyze the stages of professional guidance (OP) in Cuba and its particularities in Santiago de Cuba. A descriptive methodology with chronological and qualitative perception was applied, through the analysis of documents specialized in the subject. Theoretical methods were applied such as analysis-synthesis, induction-deduction and the historical-logical method that allowed a chronological analysis of the evolution of the professional orientation process. As main findings, we find that the published works, generally adjudicate the institutionalization of the process to the United States, ignoring background of the eighteenth century in Latin America. literature review evidence, the institutionalization of the process in the american continent, before the institutionalization of the term that defines it. In Cuba, and specifically in Santiago de Cuba, it is significant the creation in 1855 of an institution to guide professionally. In conclusion, he assured himself, that the OP It found special attention in Santiago de Cuba, a territory with the privilege of being the first region of Cuba with a center specifically dedicated to the OP (the General Preparatory School). Activity that will be strengthened with the foundation of the Universidad de Oriente as a public institution of higher level in 1947.